Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.bcp.2009.06.105
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin derivatives: Molecular basis of their anti-cancer activity

Abstract: Curcumin, a phenolic compound from the plant Curcuma longa L., has shown a wide-spectrum of chemopreventive, anti-oxidant and anti-tumor properties. Although its promising chemotherapeutic activity, preclinical and clinical studies highlight Curcumin limited therapeutic application due to its instability in physiological conditions. To improve its stability and activity, many derivatives have been synthesized and studied, among which bis-DemethoxyCurcumin (bDMC) and diAcetylCurcumin (DAC). In this report, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
129
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(146 citation statements)
references
References 44 publications
8
129
0
Order By: Relevance
“…Nonetheless, curcumin also may induce apoptosis in tumor cells, potentiate apoptosis induction by classical chemotherapeutic drugs, or both, supporting its potential use in anticancer therapies (Limtrakul, 2007;Reuter et al, 2008). In fact, in spite of its poor stability and bioavailability (Anand et al, 2007;Basile et al, 2009), the antitumor efficacy of curcumin has been proved in animal models and phase I clinical trials with multiple types of cancer (Anand et al, 2008). As with other plant-derived polyphenols, the proapoptotic action of curcumin has been largely attributed to the inhibition of defensive signaling pathways such as PI3K/ Akt and NF-B (Lin, 2007;Reuter et al, 2008), but other mechanisms may be equally important.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, curcumin also may induce apoptosis in tumor cells, potentiate apoptosis induction by classical chemotherapeutic drugs, or both, supporting its potential use in anticancer therapies (Limtrakul, 2007;Reuter et al, 2008). In fact, in spite of its poor stability and bioavailability (Anand et al, 2007;Basile et al, 2009), the antitumor efficacy of curcumin has been proved in animal models and phase I clinical trials with multiple types of cancer (Anand et al, 2008). As with other plant-derived polyphenols, the proapoptotic action of curcumin has been largely attributed to the inhibition of defensive signaling pathways such as PI3K/ Akt and NF-B (Lin, 2007;Reuter et al, 2008), but other mechanisms may be equally important.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been reported that curcumin has poor bioavailability in animal models and humans (28). This limitation has led researchers to generate a variety of synthetic analogues of curcumin, and investigate their capability to affect a number of molecular pathways implicated in tumorigenesis and cancer progression (29)(30)(31)(32). Typical structure modifications include the introduction of substituents on the phenyl rings and modifications of the length of the linker between the phenyl rings.…”
Section: Discussionmentioning
confidence: 99%
“…The polyphenolic compound curcumin is isolated from turmeric (Curcuma longa), a member of the ginger family, and has antioxidant (Ruby, Kuttan, Babu, Rajasekharan, & Kuttan, 1995), anti-inflammatory (Lantz, Chen, Solyom, Jolad, & Timmermann, 2005) and anti-cancer (Basile et al, 2009;Shi et al, 2006) properties. Curcumin's poor aqueous solubility, degradation and low bioavailability are obstacles for its uses in medicine (Basile et al, 2009). Camel β-casein micelles' ability to entrap curcumin was investigated, revealing that the micelle-curcumin interactions are mainly hydrophobic, critical to bioactive solubilisation ability, and ultimately its bioavailability and antioxidant activity (Esmaili et al, 2011).…”
Section: Caseinmentioning
confidence: 99%